'n Ekologiese perspektief op die straatkindverskynsel - Louw, Susanna (University of the Free State, 2008)
The purpose of this research is to look at the street child manifestation from an ecological perspective in order to obtain indicators which are important to an intervention plan for street children. The ecological perspective is utilised as a frame for the investigation, since it provides a complete holistic and systematic frame and does not proceed in a linear dimension of merely cause and effect. This perspective has resulted in the research being very meaningful since the totality of the street child has been taken into consideration and a comprehensive intervention plan, including every aspect of the child could be compiled. The literature study, as well as the empirical investigation, took place on four different levels of the ecological perspective, namely the micro-, meso-, exo- and macro levels. The micro-system is based on the following aspects, namely the physiological aspects, cognition, social emotional aspects and personality. With respect to the micro-level, the street child is exposed to much trauma and losses. The child is deprived and interventions are required in order to provide this child with care, healing, development of self and the building of relationships. In the meso-system the following systems are included viz. the family, school and peer group since these are the closest to the street child. In this meso-system it has been found that the child suffers many losses. There are practically no family structures in the world of the street child. The school is an important system in order to develop the child and train him for the labour market. The peer group plays an important role in the child’s bonding and support on the street. In the meso-system it has been found that the child must receive specific interventions which will stimulate his feeling of belonging, address his education as well as his development regarding his life skills. Regarding the exo-system, specific attention was given to the following systems: the community, public, SAPS, health, social services, religious institutions, business and habitat. It was found that the exo-system does not provide a support system to the street child. He lives isolated from support, nor does he utilise the positive systems such as health services and the church which are available for his development. In his original community there is also no support network. It is therefore important that a support system be created in the intervention in order to stimulate and support the child’s development. A support system or positive network also provides meaning to his life and gives him hope, which motivates him with regard to his own life and future. The macro-system is, for the purposes of this study, represented by acts/policy, culture, politics and religion. In South Africa the macro-system is directed to the protection and development of structures and policy with respect to children. The execution of this policy is hampered by deficient manpower and finances. The macro-system must be applied in such a manner that the street child is protected and also facilitates his development. It was concluded that the intervention with the street children should be handled by a specialist team, as well as by members of the community. The interventions must be specifically directed to the micro-system, the care, healing, bonding with other systems and the development of the child. Regarding the meso-system, focus is on development of the feeling of belonging, training and further development of life skills. Regarding the exo-system, the interventions are handled by means of a multidisciplinary team as well as community members and resources, all directed to support. The development of the support system will then contribute to creating hope in the child. In the macro-system the intervention is directed to safeguarding the street child and developing systems and policies which are to the advantage of the street child. The ecological perspective offers a comprehensive framework within which the street child may be treated as a creature of totality.

Die doel van die navorsing was om deur middel van ‘n verkennende, beskrywende en beperkte verklarende ondersoek ‘n ekologiese perspektief op die straatkindverskynsel daar te stel ten einde indikatore vir ‘n maatskaplikewerkintervensieprogram te formuleer. ‘n Beperk kwantitatiewe navorsing is gedoen deur die opstel, voltooiing, verwerking en interpretasie van ‘n vraelys voltooi deur 10 programbestuurders betrokke by verskillende programme, geregistreer by die “National Allience for Street Children (NASC)”. ‘n Kwalititatiewe navorsing het geskied deur gevallestudies by ses straatkinders betrokke by die straatkinderprogram in Bloemfontein, Vrystaat, Suid-Afrika. As resultaat van die studie is indikatore vir ‘n intervensieplan aan straatkinders saamgestel. Die intervensieplan is toepaslik gemaak op die mikro-, meso-, ekso- en makrosisteme van die straatkind. Daar is tot die gevolgtrekking gekom dat die intervensie met die straatkind deur ‘n span kundiges, sowel as gemeenskapslede hanteer moet word. Die intervensies moet spesifiek gerig word op die mikrosisteem, die versorging, genesing, binding met ander sisteme en die ontwikkeling van die kind. Ten opsigte van die mesosisteem – op die ontwikkeling van die gevoel van behoort aan, opleiding van die straatkind en verdere ontwikkeling van lewensvaardighede. Ten opsigte van die eksosisteem, word die intervensies deur middel van ‘n multi-dissiplinêre span sowel as gemeenskapslede en -bronne ook gerig op ondersteuning, ontwikkeling van die ondersteuningstelsel wat dan bydra tot die skep van hoop vir die kind. By die makrosisteem word die intervensie gerig op beskerming van die straatkind en ontwikkeling van stelsels en beleid tot voordeel van die straatkind. Die ekologiese perspektief bied ‘n volledige raamwerk waarteen die straatkind, as totaliteitswese hanteer word.
Thesis (Ph.D. (Social Work))--University of the Free State, 2008
Keywords: Street children -- Services for -- South Africa; Abandoned children -- South Africa; Social group work; Human ecology